2016
DOI: 10.1111/agec.12226
|View full text |Cite
|
Sign up to set email alerts
|

Are French consumers ready to pay a premium for eco‐labeled seafood products? A contingent valuation estimation with heterogeneous anchoring

Abstract: International audienceCould the future French eco-label for fresh seafood products find its place in the French market? This study employs a contingent valuation method to estimate French consumers’ willingness-to-pay (WTP) for eco-labeled fresh seafood products. We exploit original data from a survey carried out in 2010, where 626 participants responded to a double-bounded dichotomous choice model, through an ascending or descending bid system. Controlling for shift and anchoring effects in random effect prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 58 publications
5
16
0
3
Order By: Relevance
“…The previous studies found that the premium for EFPs ranges from 2.5 to 16.0% of the price for the non-EFP (e.g. see Loureiro & Lotade 2005;Bernab eu et al 2008;Salladarr e et al 2016). Thus, our finding of 10.7% falls within the scope of the previous studies' findings.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The previous studies found that the premium for EFPs ranges from 2.5 to 16.0% of the price for the non-EFP (e.g. see Loureiro & Lotade 2005;Bernab eu et al 2008;Salladarr e et al 2016). Thus, our finding of 10.7% falls within the scope of the previous studies' findings.…”
Section: Discussionsupporting
confidence: 85%
“…; Salladarré et al . ). Thus, our finding of 10.7% falls within the scope of the previous studies’ findings.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Sustainability labelling is a market-based instrument promoting sustainable fisheries [ 24 , 25 ], considered an incentive for a responsible management of fisheries [ 26 , 27 ] as it decreases the information gap between producers and consumers [ 28 ]. Specifically, eco-labels are becoming an important attribute of fish choice, and preferences over eco-labelled seafood products have been studied for wild [ 20 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] and farmed species [ 20 , 41 , 42 , 43 , 44 ]. Other authors showed that most consumers associate sustainability labels on food products with aspects of environmental protection rather than ethical issues [ 4 ]; this also translates to a lower willingness to pay (WTP) for social benefits of sustainability rather than for ecological benefits [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, several studies investigated worldwide the consumer"s awareness and willingness to pay for sustainable seafood (Johnston et al, 2001;Johnston & Roheim, 2006;Erwann, 2009;Goyert et al, 2010;Masahiko, 2010;Roheim et al, 2011;Davidson et al, 2012;Xu et al, 2012;Fernández-Polanco et al, 2013;Sogn-Grundvåg et al, 2013;Uchida et al, 2014;Fonner & Sylvia, 2015;Blomquist et al, 2015;Salladarré et al, 2016, McClenachan et al, 2016Bronnmann & Asche, 2016;Zhou et al, 2016;Rickertsen et al, 2017;Sun et al, 2017;Vitale et al, 2017), showing as these aspects may not directly translated into sustainable consumer behavior (World Business Council for Sustainable Development, 2008;Clonan et al, 2011;Nguyen et al, 2010;Brécard et al, 2012;Richter et al, 2017). Indeed, the sustainable seafood consumption is a very intricate process, where different factors (intentions, attitudes, social norms, trust, knowledge, habits, situational and socioeconomic conditions) and their interactions can influence the consumer"s behavior (fig 1; Richter et al, 2017).…”
Section: Introductionmentioning
confidence: 99%